ANALISIS NON LINIER KINERJA STRUKTUR PORTAL BRESING DAN PORTAL DINDING GESER AKIBAT BEBAN GEMPA KUAT - Fauzan, Muhammad
Abstract: Brace frame and shear wall frame are other alternative election of structure system in arrest for strong lateral force (seismic force). Installation of brace nor shear wall make the structure have the large stiffness. For the structure of high building, stiffness have the very important role, especially to fulfill useworthy conditions and damage control. In this thesis writing, with refer to the analysis of structure response conducted to system of structure brace frame and shear wall frame. Analysis is using static nonlinear with three encumbering pattern that is force of static ekuivalen seismic with is taken away from regulation SNI 03-1726-2002, force of static ekuivalen seismic which result from analysis of manner response spectrum (SRSS) and force of static ekuivalen seismic from regulation IBC-2003 (uniform), yielding capacity curve. Method of capacity spectrum will be got level of structure performance effect of influence plan seismic. Result of the structure response will be verification to result analysis of dynamic nonlinear time history, with artificial seismic regional of seismic 6 which is made by response spectrum plan seismic regional of seismic 6 by using program of SIMQKE. Result of structure displacement analysis of static nonlinear using capacity spectrum method at shear wall frame is enough conservative while at better brace frame using analysis of dynamic nonlinear time history.